Grammatical Errors Analysis on Students’ Descriptive Texts - Siti Sakdidah; Entika Fani Prastikawati; Faiza Hawa (Wanastra: Jurnal Bahasa dan Sastra, 2023)
Writing and grammar become students' difficulties in learning English. The purpose of this article is to identify the types of grammatical errors that students make. The methodology is descriptive-qualitative. This research is based on descriptive text written by class VII students of SMP Negeri 6 Semarang as a data source. Information was analyzed using Dulay's (1982) error theory and a taxonomy of surface strategies. The results show that the most common type of grammatical error is omission, accounting for 56 errors and about 57% of all errors. Thus, there are 20% addition errors, 14% information errors, and 9% misordering errors. The reason why omission is higher and misordering is most rarely found is because in omission, students are less thorough in using punctuation, articles, prepositions, capital letters, and the simple present tense. Furthermore, misordering was found to be very rare because students misplaced grammar, such as when using word-to-word translation from Indonesian to English.